202k views
21 votes
Simplify the expression​

Simplify the expression​-example-1
User Atorscho
by
6.1k points

1 Answer

3 votes

Answer:

-4sin(2x)

Explanation:

Angle sum identities can be used to simplify this expression.

  • cos(a+b) = cos(a)cos(b) -sin(a)sin(b)
  • sin(a+b) = sin(a)cos(b) +sin(b)cos(a)
  • sin(2x) = 2sin(x)cos(x)

Numerator

The cosine function is even, so cos(-x) = cos(x). The cosine of the sum is ...

cos(90°+x) = cos(90°)cos(x) -sin(90°)sin(x) = -sin(x)

Then the numerator simplifies to ...

4cos(-x)cos(90°+x) = -4cos(x)sin(x) = -2sin(2x)

Denominator

Matching the denominator expression to the sine of a sum relation, we see

sin(30° -x)cos(x) +sin(x)cos(30° -x) = sin((30°-x) +x) = sin(30°) = 1/2

Simplified Expression

The simplified expression is the ratio of the simplified numerator to the simplified denominator:

= -sin(2x)/(1/2)

= -4sin(2x)

User Franksort
by
5.6k points